Exploring Algebraic Properties and the Applications of Chinese Remainder Theorem - Maharani, Saskia Putri; Kurniadi, Edi; Sylviani, Sisilia (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
This research aims to identify the algebraic properties of the Chinese Remainder Theorem or CRT. Chinese Remainder Theorem is an ancient mathematical theorem that allows the solution of a system of simultaneous equations with different modules and allows the reconstruction of integers within a certain range of remainders modulo to relatively prime modulo. The method used in this research is literature study. This theorem allows for efficient processing and manipulation of integers with very large sizes. The proof of the theorems in Chinese Remainder Theorem is also presented in this research.